2023
DOI: 10.1123/ijsnem.2022-0255
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ketone Monoester Supplementation Impairs 20-min Time-Trial Performance in Trained Cyclists: A Randomized, Crossover Trial

Abstract: Acute ketone monoester (KE) supplementation can alter exercise responses, but the performance effect is unclear. The limited and equivocal data to date are likely related to factors including the KE dose, test conditions, and caliber of athletes studied. We tested the hypothesis that mean power output during a 20-min cycling time trial (TT) would be different after KE ingestion compared to a placebo (PL). A sample size of 22 was estimated to provide 80% power to detect an effect size dz of 0.63 at an alpha lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…The beneficial effects of exogenous ketones on endurance are still under debate. Some studies have reported an impairment in performance during high-intensity cycling (Leckey et al, 2017;McCarthy et al, 2023;O'Malley et al, 2017;Poffé, Wyns, et al, 2021). Conversely, other trials found no beneficial effects after acute ketone supplementation in cycling during a 15-min TT at the end of a 3 hr and 15 min simulated cycling race (Poffé et al, 2020), or 10-km running (Evans et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of exogenous ketones on endurance are still under debate. Some studies have reported an impairment in performance during high-intensity cycling (Leckey et al, 2017;McCarthy et al, 2023;O'Malley et al, 2017;Poffé, Wyns, et al, 2021). Conversely, other trials found no beneficial effects after acute ketone supplementation in cycling during a 15-min TT at the end of a 3 hr and 15 min simulated cycling race (Poffé et al, 2020), or 10-km running (Evans et al, 2019).…”
Section: Discussionmentioning
confidence: 99%